Trypanosoma cruzi, Chagas disease and cancer: putting together the pieces of a complex puzzle - Kaufman, Cintia Daniela (2023)
Considering the extensive and widespread impact on individuals, cancer can presently be categorized as a pandemic. In many instances, the development of tumors has been linked to endemic microbe infections. Among parasitic infections, Trypanosoma cruzi stands out as one of the most extensively discussed protozoans in the literature that explores the association between diseases of parasite origin and cancer. However, the effective association remains an unsolved paradox. Both the parasite, along with protozoan-derived molecules, and the associated antiparasitic immune response can induce alterations in various host cell pathways, leading to modifications in cell cycle, metabolism, glycosylation, DNA mutations, or changes in neuronal signaling. Furthermore, the presence of the parasite can trigger cell death or a senescent phenotype and modulate the immune system, the metastatic cascade, and the formation of new blood vessels. The interaction among the parasite (and its molecules), the host, and cancer undoubtedly encompasses various mechanisms that operate differentially depending on the context. Remarkably, contrary to expectations, the evidence tilts the balance toward inhibiting tumor growth or resisting tumor development. This effect is primarily observed in malignant cells, rather than normal cells, indicating a selective or specific component. Nevertheless, nonspecific bystander mechanisms, such as T. cruzi’s adjuvancy or the presence of proinflammatory cytokines, may also play a significant role in this phenomenon. This work aims to elucidate this complex scenario by synthesizing the main findings presented in the literature and by proposing new questions and answers, thereby adding pieces to this challenging puzzle.